Strategy For Strengthening Farmer Groups In Sustainable Water Resource Management In Lempuing District, OKI Regency - Mohammad Fauzan Muzaki; Lala M Kolopaking; Manuntun Parulian Hutagaol (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Water resources are a crucial element in supporting the agricultural sector. The success of agricultural development is determined by water availability, as it is crucial for production activities. Unpredictable climate change significantly impacts various agricultural activities, particularly agricultural cultivation, which ultimately impacts agricultural productivity. Water resource management itself is an effort to plan, implement, monitor, and evaluate the process of water resource conservation, water resource use, and control of damaged water resources. This research focuses on strengthening the role of farmer groups in managing water resources sustainably through capacity building and community organization. The main objectives of this research are to identify challenges faced by farmer groups by examining the level of farmer participation, evaluate the effectiveness of existing programs using the SROI method, and design more effective and sustainable capacity-building strategies through a SWOT analysis.